Diagnóstico del potencial agroindustrial de sunfo (Clinopodium nubigenum) y eneldo (Anethum graveolens) - Caguana Lagua, Manuel Arturo (2017)
The present project of the potential diagnosis agroindustrial of sunfo (Clinopodium nubigenum) and dill (Anethum graveolens) took as a target to encourage the industrialization and investigation of these plants for the components that it possesses, this was realized by the information raising applying surveys in the community of Planchaloma, parish of Toacazo, canton Latacunga. By means of the obtained results of the realized surveys it was proved that the persons of the community have knowledge of the plants, in its use it is medicinal, the type of soil is clayish and its climate is cold where it develops, with the obtained information each of the plants were sent to the Laboratory LACONAL to realize the physical and chemical analysis. The analyses physicist chemists who were obtained of the sunfo (Clinopodium nubigenum) were: ashes, 6,97 %, proteins, 4,12 %, moisture, 64,7 %, fat, 0,430, raw fibre, 7.06, entire carbohydrates 16,7 %, energy in Kj / 100g, 365 and in Kcal / 100g, 87 and of the dill (Anethum graveolens): ashes, 2,12 %, proteins, 4,91 %, moisture, 84,2 %, fat, 0,199, raw fibre, 2,73, entire carbohydrates 5,8 %, energy in Kj / 100g, 187 and in Kcal / 100g, 45). With the analyses obtained in the laboratory of each of the plants one can identify the potential agroindustrial that they present like the tea of sunfo and dill, and the extraction of the essential oil of sunfo.